Tangeretin Alleviates Cisplatin-Induced Acute Hepatic Injury in Rats: Targeting MAPKs and Apoptosis - Omar, Hany A. (PLoS One, 2016)
Despite its broad applications, cisplatin affords considerable nephro- and hepatotoxicity through triggering inflammatory and oxidative stress cascades. The aim of the current investigation was to study the possible protective effects of tangeretin on cisplatin-induced hepatotoxicity. The impact of tangeretin on cisplatin-evoked hepatic dysfunction and histopathologic changes along with oxidative stress, inflammatory and apoptotic biomarkers were investigated compared to silymarin. Tangeretin pre-treatment significantly improved liver function tests (ALT and AST), inhibited cisplatin-induced lipid profile aberrations (total cholesterol and triglycerides) and diminished histopathologic structural damage in liver tissues. Tangeretin also attenuated cisplatin-induced hepatic inflammatory events as indicated by suppression of tumor necrosis factor-α (TNF-α) and enhancement of interleukin-10 (IL-10). Meanwhile, it lowered malondialdehyde (MDA), nitric oxide (NO) and nuclear factor erythroid 2-related factor 2 (NRF-2) levels with restoration of glutathione (GSH), and glutathione peroxidase (GPx). Regarding mitogen-activated protein kinase (MAPK) pathway, tangeretin attenuated cisplatin-induced increase in phospho-p38, phospho-c-Jun N-terminal kinase (p-JNK) and phospho-extracellular signal-regulated kinase (p-ERK1/2) in liver tissues. In addition, tangeretin downregulated Bax expression with augmentation of Bcl-2 promoting liver cell survival. Our results highlight the protective effects of tangeretin against cisplatin-induced acute hepatic injury via the concerted modulation of inflammation, oxidative stress, MAPKs and apoptotic pathways.